Competing Symmetry Breaking and Spin Crossover in [FeH2L2–Me](ClO4)2. Issue 5 (1st October 2012) - Watanabe, Hiroshi; Bréfuel, Nicolas; Collet, Eric; Toupet, Loïc; Tanaka, Koichiro; Tuchagues, Jean‐Pierre
Abstract: In this contribution, we describe the symmetry breaking that appears in the low‐spin phase of the spin crossover (SC) complex [FeH2 L 2–Me ](ClO4 )2, [H2 L 2–Me = Bis[(2‐methylimidazol‐4‐yl)methylidene]‐3‐aminopropylethylenediamine], for which low‐spin (LS) to high‐spin (HS) transition may be thermally activated or photoinduced. In the LS phase stable at low temperature, a symmetry breaking occurs at around 120 K, while in the photoinduced HS (PIHS) state the high symmetry is recovered. The relaxation from this PIHS state to the LS low‐symmetry phase occurs through an intermediate LS high‐symmetry phase. The sequence of phases was evidenced by using magnetic susceptibility, X‐ray diffraction, and infrared spectroscopy data. Abstract : A symmetry breaking occurs at about 120 K in the low‐spin (LS) phase of [FeH2 L 2–Me ](ClO4 )2 . The thermally activated (ta) LS phase is of low symmetry (ls), while the photoinduced (PI) state is of high symmetry (hs). Relaxation from PIHS to LSls occurs via an intermediate LShs phase. LSls and LShs are metastable phases, and their competition depends on temperature and on the history of the material.